ENHANCHING MENTORSHIP FOR SMALL FOOD BUSINESS: ROLE OF INTERACTION FREQUENCY ON ENTREPRENEURIAL EFFORT AND COMMITMENT - Nurdin, Qamariyah; Syahbana Rusli, Meika; Yuliasih, Indah (Jurnal Teknologi Industri Pertanian, 2025)
Small food businesses often face challenges due to limited resources and capacity, making it difficult to maintain consistent effort and achieve long-term goals. Effective mentorship has emerged as a crucial solution. Small food businesses often face challenges due to limited resources and capacity, making it difficult to maintain consistent effort and achieve long-term goals. Effective mentorship has emerged as a crucial solution. This research examined the direct impact of interaction frequency on entrepreneurial effort and its influence on task completion and venture goal commitment within the context of small food businesses. The study also considers the moderating roles of mentor attitude, entrepreneurial experience, and business profile. Data were collected from 111 small food industry owners in Indonesia using the Experience Sampling Methodology through longitudinal diary studies. The findings demonstrate that frequent mentor-mentee interactions significantly enhance entrepreneurial effort, leading to improved task completion. However, effort did not have a significant direct effect on venture goal commitment. This might be attributed to factors such as perceived steady progress and the entrepreneur's belief in achieving the goals. Moderation analysis reveals that entrepreneurial experience and business profile significantly moderate the relationship between interaction frequency and effort, while mentor attitude does not. These findings highlight the importance of maximising interaction frequency with mentors to improve business performance. Mentorship programs should be tailored to the entrepreneur's experience level and the business's profile. Instead of a one-size-fits-all approach, mentorship formats and materials should be adjusted based on the business's developmental stage. Keywords: mentor-mentee interaction frequency, entrepreneurial effort, small food businesses, mentorship